The Japanese Society for Apheresis clinical practice guideline for therapeutic apheresis. Issue 6 (7th December 2021) - Abe, Takaya; Matsuo, Hidenori; Abe, Ryuzo; Abe, Shinji; Asada, Hiroaki; Ashida, Akira; Baba, Akiyasu; Eguchi, Kei; Eguchi, Yutaka; Endo, Yoshihiro; Fujimori, Yoshihiro; Furuichi, Kengo; et al.
Abstract: Most of the diseases for which apheresis therapy is indicated are intractable and rare, and each patient has a different background and treatment course prior to apheresis therapy initiation. Therefore, it is difficult to conduct large‐scale randomized controlled trials to secure high‐quality evidence. Under such circumstances, the American Society for Apheresis (ASFA) issued its guidelines in 2007, which were repeatedly revised until the latest edition in 2019. The ASFA guidelines are comprehensive. However, in the United States, a centrifugal separation method is mainly used for apheresis, whereas the mainstream procedure in Japan is the membrane separation method. The target diseases and their backgrounds are different from those in Japan. Due to these differences, the direct adoption of the ASFA guidelines in Japanese practice creates various problems. One of the features of apheresis in Japan is the development of treatment methods using hollow‐fiber devices such as double filtration plasmapheresis (DFPP) and selective plasma exchange and adsorption‐type devices such as polymyxin B‐immobilized endotoxin adsorption columns. Specialists in emergency medicine, hematology, collagen diseases/rheumatology, respiratory medicine, cardiovascular medicine, gastroenterology, neurology, nephrology, and dermatology who are familiar with apheresis therapy gathered for this guideline, which covers 86 diseases. In addition, since apheresis therapy involves not only physicians but also clinical engineers, nurses, dieticians, and many other medical professionals, this guideline was prepared in the form of a worksheet so that it can be easily understood at the bedside. Moreover, to the clinical purposes, this guideline is designed to summarize apheresis therapy in Japan and to disseminate and further develop Japanese apheresis technology to the world. As diagnostic and therapeutic techniques are constantly advancing, the guidelines need to be revised every few years. In order to ensure the high quality of apheresis therapy in Japan, both the Japanese Society for Apheresis Registry and the guidelines will be inseparable.